Outcomes of Early Versus Late Tracheostomy in Patients With COVID-19: A Multinational Cohort Study. (21st November 2022) - Harrell Shreckengost, Constance S.; Foianini, Jorge Esteban; Moron Encinas, Karen Milenka; Tola Guarachi, Hugo; Abril, Katrina; Amin, Dina; Berkowitz, David; Castater, Christine Aisha; Douglas, J. Miller; Grant, April A.; Khullar, Onkar Vohra; Lane, Andrea Nichole; et al.
Abstract : OBJECTIVES: Timing of tracheostomy in patients with COVID-19 has attracted substantial attention. Initial guidelines recommended delaying or avoiding tracheostomy due to the potential for particle aerosolization and theoretical risk to providers. However, early tracheostomy could improve patient outcomes and alleviate resource shortages. This study compares outcomes in a diverse population of hospitalized COVID-19 patients who underwent tracheostomy either "early" (within 14 d of intubation) or "late" (more than 14 d after intubation). DESIGN: International multi-institute retrospective cohort study. SETTING: Thirteen hospitals in Bolivia, Brazil, Spain, and the United States. PATIENTS: Hospitalized patients with COVID-19 undergoing early or late tracheostomy between March 1, 2020, and March 31, 2021. INTERVENTIONS: Not applicable. MEASUREMENTS AND MAIN RESULTS: A total of 549 patients from 13 hospitals in four countries were included in the final analysis. Multivariable regression analysis showed that early tracheostomy was associated with a 12-day decrease in time on mechanical ventilation (95% CI, –16 to –8; p < 0.001). Further, ICU and hospital lengths of stay in patients undergoing early tracheostomy were 15 days (95% CI, –23 to –9 d; p < 0.001) and 22 days (95% CI, –31 to –12 d) shorter, respectively. In contrast, early tracheostomy patients experienced lower risk-adjusted survival at 30-day post-admission (hazard ratio, 3.0; 95% CI, 1.8–5.2). Differences in 90-day post-admission survival were not identified. CONCLUSIONS: COVID-19 patients undergoing tracheostomy within 14 days of intubation have reduced ventilator dependence as well as reduced lengths of stay. However, early tracheostomy patients experienced lower 30-day survival. Future efforts should identify patients most likely to benefit from early tracheostomy while accounting for location-specific capacity.